Regional blockade in endoscopic surgical removal of pituitary adenoma - Akhmadov, N; Nasibova, E (Pain medicine, 2025)
Backround. The endoscopic endonasal transsphenoidal approach is gaining popularity as an alternative to the traditional technique for removing pituitary adenomas using an operating microscope. In transnasal transsphenoidal resection of pituitary tumors, bilateral regional anesthesia of the pterygopalatine fossa, performed through subzygomatic access, has been found to be the most optimal technique. Methods. To investigate the effectiveness of combining regional anesthesia with general anesthesia in reducing intraoperative drug administration and minimizing patient stress, two groups of patients were formed. Group I (n=14) received general anesthesia, while Group II (n = 23) underwent bilateral regional anesthesia of the pterygopalatine fossa in addition to general anesthesia, along with nasal mucosa application anesthesia. Results. The results of the study indicate that the inclusion of regional blockade in the general anesthesia protocol is advisable for the removal of pituitary adenomas using the endoscopic transnasal transsphenoidal approach. This approach ensures hemodynamic stability and reduces the drug load during the operation. Conclusions. In conclusion, the combination of regional anesthesia with general anesthesia ensures hemodynamic stability during both the intraoperative and postoperative periods.